Analyzing the Future Climate Change Impacts on Meteorological Parameters Using the LARS-WG Model - Dheyaa, Mohammed A.; Al-Mukhtar, Mustafa M.; Shemal, Khalid (Salehan Institute of Higher Education, 2024)
This research aims to evaluate the impacts of climate changes and reveal the future trends on meteorological parameters, i.e., precipitation and temperature effects, in three major cities in Iraq, namely Baghdad, Wasit, and Maysan, which are located along the Tigris River basin. The LARS-WG8.0 model was employed, and five GCMs were used within CMIP6 under three different scenarios, i.e., SSP126, SSP245, and SSP585, for the period 2021-2100. The observed and simulated data were tested by the statistical criteria R, R2, NSE, and RMSE through the baseline period 2003-2022. In addition, using the K-S test for validation of the LARS-WG8.0 model resulted in accuracy and reliability. The future projections indicate that the average temperatures will increase until the end of the current century, with a difference of 1.86, 2.85, and 5.36°C. The fluctuations in precipitation occur throughout the winter, spring, and autumn months. The highest precipitation was recorded in December and January. Therefore, all GCMs give a unified indicator of future climate forecasts. Rising temperatures and fluctuations in precipitation negatively impacted water and food security. As a result, this will impact the water resources and agricultural sectors. This research contributes to exploring the future climate behavior of the study area. Doi: 10.28991/CEJ-2024-010-11-019 Full Text: PDF